2002
DOI: 10.1016/s0006-291x(02)00767-2
|View full text |Cite
|
Sign up to set email alerts
|

Lys 43 and Asp 46 in α-helix 3 of uteroglobin are essential for its phospholipase A2 inhibitory activity

Abstract: Uteroglobin (UG) is an anti-inflammatory, secreted protein with soluble phospholipase A 2 (sPLA 2 )-inhibitory activity. However, the mechanism by which UG inhibits sPLA 2 activity is unknown. UG is a homodimer in which each of the 70-amino acid subunits forms four a-helices. We previously reported that sPLA 2 -inhibitory activity of UG may reside in a segment of a-helix 3 that is exposed to the solvent. In addition, it has been suggested that UG may inhibit sPLA 2 activity by binding and sequestering Ca þþ , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…Interestingly Chowdhury et al demonstrated that residues Lys43 and Asp46 in the α-helix 3 of uteroglobin are essential for its PLA 2 -inhibitory activity. 29,31 The independent or simultaneous mutation of Lys43 and Asp46 to a glutamate and a lysine, respectively, resulted in the alteration of the capacity of uteroglobin to inhibit PLA 2 . 31 Molecular modeling of the substitution of Asp46 to a lysine in the crystal structure of Fel d 1 suggested that this residue confers the right conformation to the calcium-binding site (data not included).…”
Section: The Binding Of a Ca 2+ In The Dimerization Interface Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly Chowdhury et al demonstrated that residues Lys43 and Asp46 in the α-helix 3 of uteroglobin are essential for its PLA 2 -inhibitory activity. 29,31 The independent or simultaneous mutation of Lys43 and Asp46 to a glutamate and a lysine, respectively, resulted in the alteration of the capacity of uteroglobin to inhibit PLA 2 . 31 Molecular modeling of the substitution of Asp46 to a lysine in the crystal structure of Fel d 1 suggested that this residue confers the right conformation to the calcium-binding site (data not included).…”
Section: The Binding Of a Ca 2+ In The Dimerization Interface Resultsmentioning
confidence: 99%
“…29, 30 Chowdhury et al thereafter assessed the critical role of residues Lys43 and Asp46 of uteroglobin for its PLA 2 -inhibitory activity. 31 Modulation of PLA 2 may affect the biosynthesis of eicosanoids and platelet-activating factors, potent mediators of inflammatory and allergic responses. 32 Uteroglobin only inhibits the function of the enzyme PLA 2 when the concentration of Ca 2+ , an essential cofactor for PLA 2 , becomes limiting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equal amounts (20 g) of the total protein derived from cell lysate of each sample were loaded in the gel and resolved by electrophoresis using 4 -12% bis-Tris NuPage gel (Invitrogen Life Technologies) under denaturing and reducing conditions and the proteins transferred onto polyvinylidene difluoride membranes (Amersham Biosciences) (36). The immunoblot analysis was then conducted using specific Abs against TCR (clone 6B10.2).…”
Section: Western Blot Analysesmentioning
confidence: 99%
“…This peptide corresponds to the nine C-terminal amino acids of ahelix 3 of CC10 (Chowdhury et al, 2002). It has been implicated in a broad range of cellular functions, including potent PLA2 inhibition, anti-inflammatory activities and regulating the expression of adhesion molecules on human leukocytes (Miele et al, 1990;Miele, 2000;Zouki et al, 2000).…”
Section: Introductionmentioning
confidence: 99%